Does Mentoring Matter? On the Way to Collaborative School Culture - Eve Eisenschmidt; Tuuli Oder (ÜNİVERSİTEPARK Limited, 2018)
This study investigates beginning teachers' relationships with their mentors as well as the collaboration between beginning teachers and their colleagues after five years of practice. One of the important roles of a mentor is to support the beginning teachers' collaboration with other teachers. Authors investigated the sustainability of the collaborative aspect of the induction program in order to determine if collaboration between beginning teachers and their mentors continues after five years of work and whether this collaboration extends to the beginning teachers' colleagues. Open-response questions were chosen for discovering aspects related with the continuity of mentoring. More than a half of the beginning teachers continue collaboration with their mentors throughout a five-year period. These beginning teachers, whose collaboration with their mentors continues during the five years, are found to be more cooperative with other colleagues at school. One-to-one mentoring creates quality examples for teacher collaboration that are treated as the first step towards creating a professional learning community within schools. The novelty of this research lies in the longitudinal nature of the teachers who participated in the national induction year program and whose progress has been monitored throughout five years of work.